2015
DOI: 10.1371/journal.pone.0126987
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and PCR Detection Of Binary, Pir-Like Toxins from Vibrio parahaemolyticus Isolates that Cause Acute Hepatopancreatic Necrosis Disease (AHPND) in Shrimp

Abstract: Unique isolates of Vibrio parahaemolyticus (VPAHPND) have previously been identified as the causative agent of acute hepatopancreatic necrosis disease (AHPND) in shrimp. AHPND is characterized by massive sloughing of tubule epithelial cells of the hepatopancreas (HP), proposed to be induced by soluble toxins released from VPAHPND that colonize the shrimp stomach. Since these toxins (produced in broth culture) have been reported to cause AHPND pathology in reverse gavage bioassays with shrimp, we used ammonium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 17 publications
2
147
1
9
Order By: Relevance
“…They were subsequently found in other pathogenic bacteria including Vibrio parahaemolyticus , in which they play an important role in shrimp pathogenesis (Sirikharin et al, 2015). It was shown that the crystal structure of the V. parahaemolyticus Pir toxin complex resembles those of the Bacillus thuringiensis Cry toxins, suggesting that they may have a conserved mode of action that ultimately causes destabilization of the host cell cytoskeleton, leading to cell death (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They were subsequently found in other pathogenic bacteria including Vibrio parahaemolyticus , in which they play an important role in shrimp pathogenesis (Sirikharin et al, 2015). It was shown that the crystal structure of the V. parahaemolyticus Pir toxin complex resembles those of the Bacillus thuringiensis Cry toxins, suggesting that they may have a conserved mode of action that ultimately causes destabilization of the host cell cytoskeleton, leading to cell death (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…En el continente americano el AHPND se diagnosticó en el año 2013, generando altas mortalidades y disminución de producción en México, específicamente en los estados de Sonora, Nayarit y Sinaloa Nunan et al, 2014;Pantoja y Lightner, 2014;Sánchez et al, 2014;Sirikharin et al, 2015). Por último, se identificó en Centroamérica en el 2015 (Han et al, 2015b), donde no se especificó el país, pero posteriormente, se informó su presencia en los cultivos en Belice (Shrimp News International, 2015).…”
Section: Origenunclassified
“…; Sirikharin et al . ). Remarkably, the oral administration of recombinant PirA‐like toxin alone did not cause histopathological signs or mortality (Lee et al .…”
Section: Effect Of Recombinant Pira‐like Toxin Administration By Bathmentioning
confidence: 97%
“…Figure shows the patterns observed in the SDS‐PAGE analysis, where a strong band of 16 KDa is observed, which is very close to the theoretical and native PirA‐like toxin molecular weight (Sirikharin et al . ). Evaluation by SDS‐PAGE allowed to determine that PirA‐like toxin predominantly remains in the soluble fraction (data not shown).…”
Section: Effect Of Recombinant Pira‐like Toxin Administration By Bathmentioning
confidence: 97%
See 1 more Smart Citation